The Influence of Student Organizations, Role Conflict, and Self-Regulation on Students' Academic Achievement - Cahya, Septyan Budy; Wulandari, Ruri Nurul Aeni; Nurlaili, Eka Indah; Arif, Amirul; Mahendra, Angga Martha (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the influence of student organizations, role conflict, and self-regulation on student academic achievement. This study uses a quantitative approach with a survey method. The research sample consisted of 200 students of the Faculty of Economics and Business, Universitas Negeri Surabaya(Unesa) who are active in student organizations. Data collection was conducted through distributing questionnaires with a Likert scale. Data analysis used multiple linear regression, accompanied by tests of validity, reliability, normality, multicollinearity, and heteroscedasticity. The results showed that student organizations have a positive effect on student academic achievement. Role conflict has a negative effect on achievement. And self-regulation has a positive effect on academic achievement. All three variables simultaneously have a significant effect on academic achievement. The results of this study confirm that involvement in student organizations can have a positive impact on academic achievement if combined with strong self-regulation skills and effective role conflict management. Therefore, developing self-regulation skills and time management training should be part of student organization development programs in higher education.